Artificial intelligence in the cybersecurity of German Small and Medium Sized Enterprises - Dörpinghaus, Simon (2019)
With the recent boom in big data and the continuous need for innovation, artificial intelligence is carving out a bigger place in our society. Through its cognitive capabilities, it brings new possibilities to tackle many issues within organizations. In cybersecurity, artificial intelligent algorithms can over time autonomously mature with exposure to threats. Intelligent algorithms also raise new challenges about its use and limits. This dissertation aims to provide a better understanding of the role of artificial intelligence plays in cybersecurity for small and medium sized enterprises in Germany. The main research question that guides this study is: How can AI-enabled cybersecurity solutions, like machine and deep learning, help German SMEs fighting the increasing threat and past incidence of security breaches? Therefore, dissertation highlights how a deep understanding of artificial intelligence and its integration in the cybersecurity process of organizations can protect companies from the increasing threat of cyber criminality. Artificial intelligence is an efficient tool to deal with complex cyber-attacks, whereas classical, linear protection methods offer limited protection. Finally, it appears that artificial intelligence in cybersecurity also has certain limitations and needs to cater to the specificities of small and medium sized enterprises.